The Influence of Treatment Seeking Behavior on Diabetic Ulcer Risk Levels in the Service Area of Sudiang Raya Community Health Center - Ince Marni; Yusran Haskas; Indah Restika (Ammar Dharma Foundation, 2024)
Background: Diabetes mellitus is a chronic condition caused by the pancreas' inability to produce enough insulin hormone, leading to elevated blood sugar levels. Treatment-seeking behavior refers to actions or efforts taken by individuals when they are ill. Foot care is an action to maintain foot hygiene in diabetes patients and prevent early foot injuries.Objective: The aim of this study was to determine the relationship between treatment-seeking behavior and foot care on the risk of diabetic foot ulcers in the service area of Sudiang Raya Community Health Center.Method: This research used a quantitative method with a Cross-Sectional design and a population of 423. The sample consisted of 80 respondents selected through purposive sampling. Data collection was conducted using Treatment Seeking Behavior questionnaire, Appendix H The Modified Diabetic Foot Care Behavior Questionnaire, and Ipswich Touch Test (IpTT).Results: The results of this study showed that there is a relationship between treatment-seeking behavior and the risk of diabetic foot ulcers (p=0.022).Conclusion: In conclusion, there is a relationship between treatment-seeking behavior and the risk of diabetic foot ulcers in the service area of Sudiang Raya Community Health Center.